Penerapan Model Pembelajaran Jerrold E KEM Di SMP Hanuru - Novita Loma Sahertian; David Ming; Hestyn Natal Istinatun; Junio Richson Sirait (Jurnal Pendidikan Agama Kristen (JUPAK), 2021)
This study intends to apply a learning model including: development of a syllabus and a Learning Implementation Plan (RPP) cooperative type time token type in PAK and Character In Class VIII, the material of Allah loves the world. The method used in this research was the descriptive qualitative research method. Data were collected through observation, interview, and literature study and analyzed in-depth and described descriptively. The action hypothesis is a temporary answer in the form of action on the formulation of the problems set out in this classroom action research which is: student learning outcomes will increase "can be accepted. Based on the results of the implementation of classroom action research with the title implementation of the Jerrold E camp learning model in Christian education (PAK) and Character subjects in junior high schools, especially in Hauru Christian Middle School in class VIII which lasted for 2 research cycles, it can be concluded: Christian Education (PAK) and Character work effectively, so student learning outcomes will increase.